PENGEMBANGAN MODUL IPA BERBASIS INKUIRI TERBIMBING PADA MATERI KALOR DAN PERPINDAHANNYA PESERTA DIDIK KELAS VII MTs MUHAMMADIYAH JAYAPURA, PAPUA - Desvita Astari Djamion; Florida Doloksaribu (Program Magister Pendidikan IPA, Program Pascasarjana Universitas Cenderawasih, 2018)
Research and development (R & D) about learning using guided inquiry-based science module aims to (1) find out how to develop guided inquiry-based science learning modules on heat material and its transfer to students of class VII MTs Muhammadiyah Jayapura, Papua (2) Knowing the feasibility guided inquiry-based science learning modules on heat and displacementThe type of data used is primary data about the quality of module feasibility. Differences in learning outcomes are obtained from n-Gain analysis at each RPP meeting. Data retrieval is used questionnaire instrument, interviews and student learning outcomes test ..The results obtained that 1) how to develop a guided inquiry-based science learning module on heat material and its transfer to students of class VII MTs Muhammadiyah Jayapura, Papua that is they instruct the material in accordance with basic competencies and indicators. 2) guided inquiry-based Science Learning module on heat and transfer material is suitable for use at MTs Muhammadiyah Jayapura, Papua. Keywords: Guided Inquiry, Heat and Transfer